Association of cardiac troponin T and growth differentiation factor 15 with replacement and interstitial cardiac fibrosis in community dwelling adults: The multi-ethnic study of atherosclerosis - deFilippi, Christopher R.; Tran, Henry; Gattani, Raghav; Daniels, Lori B.; Shah, Palak; Ilkhanoff, Leonard; Christenson, Robert; Lima, Joao A.; Seliger, Stephen (Frontiers in Cardiovascular Medicine, 2023)
Background Subclinical abnormalities in myocardial structure (stage B heart failure) may be identified by cardiac and non-organ specific biomarkers. The associations of high-sensitivity cardiac troponin T (hs-cTnT) and growth differentiation factor-15 (GDF-15) with cardiac magnetic resonance imaging (CMR) interstitial fibrosis (extracellular volume [ECV]) is unknown and for GDF-15 the association with replacement (late gadolinium enhancement [LGE]) is also unknown. GDF-15 is a systemic biomarker also released by myocytes associated with fibrosis and inflammation. We sought to define the associations of hs-cTnT and GDF-15 with these CMR fibrosis measures in the MESA cohort. Methods We measured hs-cTnT and GDF-15 in MESA participants free of cardiovascular disease at exam 5. CMR measurements were complete in 1737 for LGE and 1258 for ECV assessment. We estimated the association of each biomarker with LGE and increased ECV (4th quartile) using logistic regression, adjusted for demographics and risk factors. Results Mean age of the participants was 68 ± 9 years. Unadjusted, both biomarkers were associated with LGE, but after adjustment only hs-cTnT concentrations remained significant (4th vs. 1st quartile OR] 7.5, 95% CI: 2.1, 26.6). For interstitial fibrosis both biomarkers were associated with 4th quartile ECV, but the association was attenuated compared to replacement fibrosis. After adjustment, only hs-cTnT concentrations remained significant (1st to 4th quartile OR 1.7, 95%CI: 1.1, 2.8). Conclusion Our findings identify that both interstitial and replacement fibrosis are associated with myocyte cell death/injury, but GDF-15 a non-organ specific biomarker prognostic for incident cardiovascular disease is not associated with preclinical evidence of cardiac fibrosis.